KONFIGURASI MESIN PRESS PERMEN TERNAK OTOMATIS BERBASIS SISTEM PNEUMATIK DENGAN TIGA AKTUATOR DOUBLE ACTING CYLINDER - Ikhwan Taufik; Nur Hidayah; Rahma Wulan Idayanti; Tri Puji Rahayu; Choirul Fatikhin (Scientific Journal of Mechanical Engineering Kinematika, 2022)
This research is an innovation carried out to meet the needs of animal feed. The way is to make feed supplements in the other various forms, like animal candy, molasses block, etc. The manufacture of feed supplements, which has been mostly done manually or by simple pressing machine. The making of animal candy was developed using an automatic animal candy press machine based on a pneumatic system with three double-acting cylinder actuators. This research to determine the schematic diagram of the pneumatic system simulation, design of the machine configuration, and determine the theoretical cycle time in the process of making animal candy using that machine. The method is creating a sequential diagram to determine one cycle time of making a candy and helping of software to make a schematic diagram simulation. The results are the movement system of the machine in one cycle is A- C- A+ B+ B- C+ according to the sequential diagram. The theoretical time required by the three actuators to complete one cycle of making an animal candy is 13.57 seconds (switch and losses are ignored).